Meta-Analysis of Antibiotic Therapies for Helicobacter pylori Eradication - Ur Rehman, Shafee (Journal of Postgraduate Medical Institute, 2025)
Objective: This meta-analysis evaluated eradication success and resistance trends across 83 clinical studies (2015–2025) retrieved from PubMed, EMBASE, Scopus, Web of Science, and the Cochrane Library, to identify the most effective antibiotic strategies for H. pylori. Methodology: In the current research a systematic literature review was conducted through five electronic databases which included PubMed/MEDLINE and EMBASE and Scopus and Web of Science and the Cochrane Library. The research used four specific keywords which were Helicobacter pylori, antibiotic resistance, eradication therapy and treatment efficacy. The search included Boolean operators (AND/OR) and MeSH terms for appropriate applications. The search focused on peer-reviewed articles from January 2015 through January 2025. The search included studies from all languages. The current study was conducted according to PRISMA 2020 standards. Results: The 56 eligible studies in the pooled analysis showed that treatment success rates for eradication depended on the selected treatment plan and bacterial resistance patterns. The combination of clarithromycin with two other medications resulted in a 72% success rate (95% CI: 68–76%; I² = 62%) for patients with less than 15% clarithromycin resistance, compared with 85% success rate (95% CI: 81–89%; I² = 29%) in low-resistance areas. The combination of Bismuth with three other medications produced successful treatment results in all resistance levels with a 90% (95% CI: 87–93%; I² = 41%) eradication rate. The second-line treatment of levofloxacin-based regimens achieved an 80% success rate (95% CI: 76–84%; I² = 55%) and rifabutin-based treatments reached 77% (95% CI: 73–81%; I² = 47%) in cases of treatment failure. The combination of high-dose amoxicillin with a single antibiotic produced a 78% success rate (95% CI: 74–82%; I² = 52%) among patients who had restricted antibiotic use. The results showed that susceptibility-based treatment approaches outperformed standard treatment approaches (88% vs. 76%, p < 0.01; I² = 36%) which supports the need for individualized treatment plans. Conclusion: The results of the study also show that there is a need for region specific treatment guidelines based on antibiotic resistance. It is therefore recommended that in high resistance settings, bismuth quadruple therapy and levofloxacin containing regimens should be used and in low resistance settings, clarithromycin triple therapy should still be used. These findings also show that personalized treatment is important in the management of H. pylori infection and in the control of antibiotic resistance.